2020
DOI: 10.1016/j.annonc.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Time course and management of key adverse events during the randomized phase III SOLAR-1 study of PI3K inhibitor alpelisib plus fulvestrant in patients with HR-positive advanced breast cancer

Abstract: Background: Alpelisib (a-selective phosphatidylinositol 3-kinase inhibitor) plus fulvestrant is approved in multiple countries for men and postmenopausal women with PIK3CA-mutated, hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer following progression on or after endocrine therapy. A detailed understanding of alpelisib's safety profile should inform adverse event (AE) management and enhance patient care. Patients and methods: AEs in the phase III SOLAR-1 trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
0
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 11 publications
6
140
0
18
Order By: Relevance
“…Grade 4 should be managed as grade 3. If blood glucose remains above 500mg/dL, permanent discontinuation of the drug is warranted (3). Metformin is the first line treatment (3).…”
Section: Discussionmentioning
confidence: 99%
“…Grade 4 should be managed as grade 3. If blood glucose remains above 500mg/dL, permanent discontinuation of the drug is warranted (3). Metformin is the first line treatment (3).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PI3K inhibitors have shown some promising efficacy in stage II-III TNBC patients whose tumors have PIK3CA mutations [ 68 , 207 , 225 ]. Following on the efficacy of alpelisib to improve PFS for HR-positive breast cancer [ 228 , 229 , 230 ], alpelisib plus nab-paclitaxel is being assessed in anthracycline-refractory TNBC with PIK3CA or PTEN mutations in a phase II trial [ 225 ]. The addition of everolimus, an mTOR inhibitor, was found to be synergistic with cisplatin and paclitaxel in the treatment of stage II/III TNBC patients.…”
Section: Emerging Targeted Therapies In Tnbcmentioning
confidence: 99%
“…In SOLAR-1, in addition to the prediabetic (FPG, 5.6 to <7.0 mmol/L and HbA1c, 5.7 to <6.5%) and diabetic (FPG, ≥7.0 mmol/L or HbA1c, ≥6.5%) status, obesity (defined as body mass index ≥30) and advanced age (≥75 years old) were also associated with higher incidence rates of grade 3/4 hyperglycemia. 80 In the earliest phase of SOLAR-1, before the protocol was amended to exclude patients with diabetes, one patient whose HbA1c was ~8% was enrolled; this patient did have grade 4 hyperglycemia, but after proper dose reduction and supervision by an endocrinologist, she was able to continue study treatment for more than 2 years. Although there are insufficient data regarding the safety of alpelisib in patients with diabetes, they should not be prohibited from using this treatment provided that careful monitoring is implemented and early endocrinologist consultation is sought.…”
Section: Clinical Practice Considerationsmentioning
confidence: 99%
“…Rugo et al reported the time course and management of the key AEs in SOLAR-1 and provided valuable clinical guidance. 80 Eighty-six participants had received prophylactic (before the onset of skin rash) anti-rash medication, among whom, 70% received anti-histamines. Compared with those (n = 198) who did not receive preventive medication, these patients experienced lower rates of any-grade rash (26.7% versus 64.1%) and grade 3 rash (11.7% versus 22.7%).…”
Section: Clinical Practice Considerationsmentioning
confidence: 99%
See 1 more Smart Citation